2011
DOI: 10.1039/c1fd00022e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous gold: a new gold catalyst with tunable properties

Abstract: Nanoporous gold (np-Au) represents a novel nanostructured bulk material with very interesting perspectives in heterogeneous catalysis. Its monolithic porous structure and the absence of a support or other stabilizing agents opens up unprecedented possibilities to tune structure and surface chemistry in order to adapt the material to specific catalytic applications. We investigated three of these tuning options in more detail: change of the porosity by annealing, increase of activity by the deposition of oxides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 44 publications
2
82
0
7
Order By: Relevance
“…In the catalytic oxidation of CO, the presence of small amounts of silver has been shown to play an important role [95,96,112]. In contrast, for methanol oxidation, increases in Ag do not improve activity [113]. Ag has also been shown to contribute to the SERS enhancement observed at nanoporous gold [114] and has also been shown to influence the electrochemically measured surface area [64,83].…”
Section: Specific Features Of Nanoporous Goldmentioning
confidence: 99%
See 2 more Smart Citations
“…In the catalytic oxidation of CO, the presence of small amounts of silver has been shown to play an important role [95,96,112]. In contrast, for methanol oxidation, increases in Ag do not improve activity [113]. Ag has also been shown to contribute to the SERS enhancement observed at nanoporous gold [114] and has also been shown to influence the electrochemically measured surface area [64,83].…”
Section: Specific Features Of Nanoporous Goldmentioning
confidence: 99%
“…There have been several approaches to deal with mass transport limitations. Increasing the pore sizes via controlled coarsening can help [113]. Early on, Ding and Erlebacher proposed the use of a two-step dealloying process to generate a multimodal pore network [119].…”
Section: Specific Features Of Nanoporous Goldmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, depositing TiO 2 or PrO 2 onto the surface of NPG could greatly enhance the reactivity for CO oxidation [101], which could be regarded as inversely RMO supported gold catalyst. The strong synergy between gold and the RMO further confirmed that the active sites for CO oxidation were located at the interfaces.…”
Section: Inversely Rmo Supported Gold Catalystsmentioning
confidence: 99%
“…for CO oxidation) is under discussion. [22][23][24][25] As another instance, reports on the mechanical strength and stiffness of nominally comparable structures disagree by up to one order of magnitude. 26,27 Therefore it is significant to note that a number of different dealloying protocols are applied within these studies.…”
mentioning
confidence: 99%